The Effectiveness of Using Besmart E-Learning on the Ease of Learning for Science Education Students at UNY - Dewi, Ermita; Nafasari, Anisa; Rahayu, Dita Puji (Jurnal Ilmiah WUNY, 2025)
Besmart UNY is a platform developed by UNY to increase the intention to use information systems in learning. This study aims to (1) determine the effectiveness of using besmart e-learning for the ease of lectures for UNY Science Education students, (2) find out the advantages and disadvantages of using besmart e-learning in UNY Science Education student lectures, (3) how to overcome weaknesses or problems in the use of learning media through besmart. This research is a qualitative research with a survey research method. The subjects of this research were Science Education students at UNY undergraduate level in 2019, 2020, 2021 and 2022 who were selected using a selection technique of 70 students. The results of this study are (1) besmart is effectively used in science education student lectures at UNY, (2) its advantages are facilitating the learning process, learning is more effective while its weaknesses are frequent errors, changes in appearance so that sometimes data or assignments that have been collected are lost, and difficult in looking for classes, (3) how to overcome weaknesses, namely improving the besmart system, adding and developing features.